1974
DOI: 10.1172/jci107836
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcium on the Inotropic Actions of Hyperosmotic Agents, Norepinephrine, Paired Electrical Stimulation, and Treppe

Abstract: A B S T R Apacing persisted in causing marked increases in developed tension and dT/dt even in the presence of D600, suggesting that their inotropic effects are not dependent on increased intracellular transfer of calcium during systole through cell membrane channels in which D600 acts as a competitive inhibitor.The results of these studies suggest that apparent functional saturation of intracellular calcium receptor sites eliminates any additional inotropic effect of hyperosmolality or paired pacing. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…Gross infarct size was not measured in either study, but the occurrence of a significant increase in left atrial mean pressure and a significant decrease in peak LV dP/dt after coronary occlusion suggest more severe LV dysfunction in the present study in comparison to earlier work (38) in which these changes were not seen. Heart rate at 1 wk was also higher (126±+9) in our study than in the earlier study ( PESP may be a result of an augmentation in slowchannel calcium entry (66), an increase in calcium release from the sarcoplasmic reticulum (67,68) or a compensatory pause following the premature stimulus (41). PESP has been demonstrated in both normal and ischemic myocardium (69) and provokes a nearly maximal contractile response in isolated, isometrically contracting papillary muscles (70).…”
Section: Discussionsupporting
confidence: 42%
“…Gross infarct size was not measured in either study, but the occurrence of a significant increase in left atrial mean pressure and a significant decrease in peak LV dP/dt after coronary occlusion suggest more severe LV dysfunction in the present study in comparison to earlier work (38) in which these changes were not seen. Heart rate at 1 wk was also higher (126±+9) in our study than in the earlier study ( PESP may be a result of an augmentation in slowchannel calcium entry (66), an increase in calcium release from the sarcoplasmic reticulum (67,68) or a compensatory pause following the premature stimulus (41). PESP has been demonstrated in both normal and ischemic myocardium (69) and provokes a nearly maximal contractile response in isolated, isometrically contracting papillary muscles (70).…”
Section: Discussionsupporting
confidence: 42%
“…Whereas gentamicin and La+++ only decreased the magnitude of the frequency-force responses, D600 converted the positive relationship to a negative relationship. Inversion of the frequency-force relationship by D600 has previously been explained by a rate-dependent inhibitory effect on Ca++ movement through the slow channels, thereby preventing refilling of other Ca++ binding sites (17,18). On the other hand, La... displaces and replaces Ca++ at various superficial membrane sites, thereby reducing net availability of Ca++ for translocation (17,19).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in both T and in (-) dP/dt35 indicated that relaxation was also enhanced. In isolated muscle preparations the Bowditch effect depends on calcium transport (40). Previously it had been shown by Koch-Weser that epinephrine release from sympathetic nerve endings plays no role in the genesis of the fundamental interval-strength relation of heart muscle (41).…”
Section: Interventions Before and After Beta-adrenergic Blockadementioning
confidence: 99%